Home Dispenser / Nurul Hidayah Rosali - Rosali, Nurul Hidayah (2020)
Nowadays, many people welcome the chance to make their daily life more convenient and one’s life a little easier. Cat owners are no exception. Pet foods and supplies have always presented as crucial challenges for both storage and food. Home Dispenser is a food dispenser that have many features and functions that are useful for the pet owner, senior citizen, and public people who have a pet. This product basically focusing on the way how the pet owner can give food to their pet during their absence at home. For the food dispenser, it is completed with a transparent container or bottle. We use the transparent one because this will easier the pet owner to watch the level of food left. The food dispenser also have a tunnel inside it, so that it can flow the food directly to the bowl. On the right side of the food dispenser, a ‘button-like’ push down that can flow the amount of food needed. Next, the place for pet to sleep. This place is located above the place the pet play. For this bed, we use a cosy cushion to makes as a bed sheet. Lastly, the place for the pet to play. We used 100 percent boxes, folded them until become compact, and circle it using a guni rope. A guni rope was the strongest rope among all of the rope such as raffia rope and so on. This rope was used as a place for the pet to scratching.